Streamlining Retail Operations: How RPA Transforms Distribution Centers and In-Store Processes - Nishanth Vepachedu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The retail industry is experiencing a fundamental transformation by adopting Robotic Process Automation (RPA) and artificial intelligence technologies. This comprehensive article examines how automation solutions revolutionize retail operations across distribution centers, in-store processes, and customer service functions. The implementation of RPA has demonstrated significant improvements in operational efficiency, cost reduction, and customer satisfaction across various retail segments. Automated systems are reshaping traditional retail paradigms, from inventory management and supply chain optimization to customer service enhancement and returns processing. Integrating AI-enhanced RPA solutions has particularly impacted pricing management, promotional campaigns, and compliance procedures, leading to substantial improvements in accuracy, efficiency, and regulatory adherence.
Keywords: Retail Automation; Robotic Process Automation (RPA); Supply Chain Optimization; Customer Experience Enhancement; Data Governance